Exploring the Factors Behind Romantic Relationship Conflicts Among University Students: A Case of Mukuba University (British Journal of Multidisciplinary and Advanced Studies, 2024)
The study sought to investigate the factors behind romantic relationship conflicts among university students. This was a case study conducted at Mukuba University. The target population was undergraduate students at Mukuba University. The sample was selected using quota sampling technique; thus, participants were selected from different schools and year of study based on their romantic relationship status. Those who had not experience romantic relationships were not part of the study. The sample size of the study was 15 students drawn from three schools. The data were collected using face-to-face interviews with the selected students.  The study identified six overarching themes, including communication issues, insecurity, time management and priorities, intimacy and sexual matters, financial issues, and cultural or religious disparities as the causes and types of conflicts. The study also revealed that communication conflicts stem from partners ignoring, providing the silent treatment, or encountering communication ambiguity. Insecurity issues arise from incidents of infidelity, suspicion, and possessiveness, while time and priority conflicts result from imbalances between academic commitments and the partners' quality time together. Moreover, the study sheds light on conflicts related to differences in sexual desires and financial discrepancies. Financial challenges include concerns about overdependence on partners for support or materialistic attitudes, often leading to conflicts. Religious and cultural disparities are also influential, as participants experienced relationship strain due to differing beliefs. Furthermore, the investigation explored the outcomes of these conflicts, categorizing them into emotional, relational, academic, mental health, and social impacts. Conflicts triggered anxiety, depression, and stress, affecting relationship stability and leading to decreased feelings of love and connection, breakup, or relationship resilience. Additionally, conflicts negatively affected academic performance and concentration, leading to stress-related physical symptoms and social isolation among individuals experiencing relationship conflicts. The coping mechanisms employed by individuals were categorized into maladaptive strategies like abuse or escapism and adaptive strategies such as seeking support and self-care/stress management. Maladaptive strategies involved aggressive behaviors and avoidance, while adaptive mechanisms included seeking external support or engaging in self-care activities as a means to manage conflict-induced stress. This study contributes to the understanding of conflicts in romantic relationships, emphasizing the complexity and diverse impact of these conflicts on individuals involved.